Pemanfaatan Sig Untuk Untuk Mengurangi Resiko Bencana Banjir Di Kota Demak - Luluk Baikuna; M. Harun Rifai; Rizqi Trisnaningtyas (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The application of Geographic Information Systems (SIG) has become an important tool in combating the risk of flood disasters in many areas, including Demak City. This research aims to explore and evaluate the possible benefits of implementing SIG to reduce the danger of flooding in Demak City. The study approaches used include stakeholder interviews, field surveys, and geographic data analysis. The research results show how useful SIG is for creating early warning systems, identifying air flow patterns, and mapping areas vulnerable to flooding. The use of SIG also enables improved coordination of flood mitigation and management among various interconnected entities. This study makes a significant contribution to our understanding of the function of geospatial information technology in disaster management and provides useful insights for stakeholders to create more effective methods for mitigating flood hazards in Demak City.